1998
DOI: 10.1152/ajpendo.1998.274.6.e1002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the protective effect of estradiol-17β on lipid peroxidation and DNA damage

Abstract: Previous studies from our laboratory have shown that estrogens can protect against lipoprotein peroxidation and DNA damage. In this study, the mechanism of estradiol-17β (E2) action was investigated by comparing E2 with selective scavengers of reactive oxygen species (ROS) in terms of inhibition of 1) human low-density lipoprotein (LDL) peroxidation (measured by the diene conjugation method) and 2) DNA damage (measured by the formation of strand breaks in supercoiled OX-174 RFI DNA). In addition, the direct ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 26 publications
5
78
0
2
Order By: Relevance
“…Furthermore, estrogen replacement in postmenopausal women has been shown to have antioxidant effects based on scavenging mechanism (Sack et al 1994), and cardioprotective effects (Stampfer et al 1991). In particular, estrogen decreases oxidative modification of low-density lipoproteins both in vitro and in vivo (Ayres et al 1998). Furthermore, beneficial effects of estrogen in Alzheimer's disease have been reported and may be partly attributable to its potent antioxidant activity (Paganini-Hill 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, estrogen replacement in postmenopausal women has been shown to have antioxidant effects based on scavenging mechanism (Sack et al 1994), and cardioprotective effects (Stampfer et al 1991). In particular, estrogen decreases oxidative modification of low-density lipoproteins both in vitro and in vivo (Ayres et al 1998). Furthermore, beneficial effects of estrogen in Alzheimer's disease have been reported and may be partly attributable to its potent antioxidant activity (Paganini-Hill 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Brain damage after TFI has been linked to enhanced leukocyte adhesion/infiltration, 19 free radical mechanisms, 20 upregulation of the inducible NOS (iNOS) isoform, 21 altered cerebral glucose transport, 22,23 and apoptosis. 24 Estrogens, E 2 in particular, have been shown to possess anti-inflammatory functions, 25 antioxidant actions, 26,27 an ability to block the induction of iNOS, 2 a capacity to improve glucose transport, 28 and antiapoptotic effects. 29,30 Because none of those possibilities were specifically addressed in this report, no further comment can be made at this time.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These findings would appear to be consistent with a nongenomic process and might be viewed as evidence of antioxidant actions of estrogens, as some investigators have suggested. 26,27,33,34 On the other hand, there are indications that E 2 -related neuroprotection, to some degree, may involve interactions with classic receptors (see, for example, Singer et al 35 ). The present finding of detectable blood E 2 levels in the OVX rats (30 pg ⅐ mL…”
mentioning
confidence: 99%
“…Estrogens have been shown to inhibit lipoprotein peroxidation in vivo and in vitro (50,51,(81)(82)(83)(84)(85)(86)(87)(88). Some clinical studies have also found that estrogen treatment inhibited the susceptibility of low-density lipoprotein to oxidative modification (50,86), whereas others found that oxidation of lowdensity lipoprotein particles was not generally influenced by estrogen (89,90).…”
Section: Epidemiology Of Breast Cancer: Role Of Lipid Peroxidationmentioning
confidence: 99%